Nicotianamine as a Potential Active Component of Lotus Seed Extract for Inhibiting Angiotensin-converting Enzyme - Nishibori, Naoyoshi; Morita, Kyoji; Sagara, Takefumi (Current Functional Foods, 2025)
AimsHypertension is one of the chronic diseases causing a serious health problem in many countries worldwide. Therefore, the prevention and amelioration of hypertension with medicinal food is considered to be important for maintaining good health and well-being. The main objective of this study is to verify that the extract of lotus seed has a significant inhibitory effect on the angiotensin I-converting enzyme (ACE).BackgroundLotus (Nelumbo nucifera) is well known to have a variety of biological and medical activities and is popularly used as a traditional medicinal food in several East Asian countries. In a previous study, we reported that the aqueous extract of lotus root used as a popular foodstuff caused an inhibitory effect on the angiotensin I-converting enzyme (ACE), suggesting its possible effectiveness for improving high blood pressure.ObjectiveThe purpose of the present study was to reveal the effect of lotus seed extract on ACE activity and to identify a potentially active component of the extract originating from lotus seed.MethodsThe ACE inhibitory activity was determined using Hippuryl-L-histidyl-L-leucin (HHL) as substrate, and the amount of hippuric acid formed enzymatically was determined using an HPLC system.ResultsThe lotus seed extract was shown to strongly inhibit the ACE activity, thus ameliorating the hypertensive state. Furthermore, the fractionation of the lotus seed extract provided evidence for suggesting nicotianamine as a putative ACE-inhibiting component contained in the extract.ConclusionThese findings were considered to propose the possibility that the lotus seed and the lotus root might benefit patients with hypertension.
Keywords: ACE inhibition